Getting ready for the guy/girl thing : two ex-teens reveal the shocking truth about God's plan for success with the opposite sex - Johnson, Greg, 1956-; Shellenberger, Susie (Ventura, Calif., U.S.A. : Regal Books, 1991)
Gives advice on various aspects of dating from a Christian perspective.
Keywords: Dating (Social customs) -- Religious aspects -- Christianity -- Juvenile literature; Teenagers -- United States -- Conduct of life; Dating (Social customs); Conduct of life; Christian life